2005
DOI: 10.1136/bmj.330.7492.625
|View full text |Cite
|
Sign up to set email alerts
|

How well does B-type natriuretic peptide predict death and cardiac events in patients with heart failure: systematic review

Abstract: Objective To assess how well B-type natriuretic peptide (BNP) predicts prognosis in patients with heart failure. Design Systematic review of studies assessing BNP for prognosis in patients with heart failure or asymptomatic patients. Data sources Electronic searches of Medline and Embase from January 1994 to March 2004 and reference lists of included studies. Study selection and data extraction We included all studies that estimated the relation between BNP measurement and the risk of death, cardiac death, sud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
398
1
19

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 633 publications
(428 citation statements)
references
References 42 publications
(62 reference statements)
10
398
1
19
Order By: Relevance
“…BNP is secreted primarily by cardiac myocytes in response to increase in LV wall stress, resulting in myocyte stretch, and the BNP level shows good correlation with LV end‐diastolic pressure. BNP levels are associated with HF severity across the spectrum of HF stages 9, 10, 11. In the current study, the BNP levels showed a significantly independent predictive value for poor prognosis in patients with HFrEF, HFpEF, and HFrlEF.…”
Section: Discussionsupporting
confidence: 54%
“…BNP is secreted primarily by cardiac myocytes in response to increase in LV wall stress, resulting in myocyte stretch, and the BNP level shows good correlation with LV end‐diastolic pressure. BNP levels are associated with HF severity across the spectrum of HF stages 9, 10, 11. In the current study, the BNP levels showed a significantly independent predictive value for poor prognosis in patients with HFrEF, HFpEF, and HFrlEF.…”
Section: Discussionsupporting
confidence: 54%
“…B-type natriuretic peptide (BNP) and the N-terminal proBNP fragment (NTproBNP) are both powerful predictors of outcome in patients with heart failure at all stages of disease [2]. Recently, data from the Framingham Heart Study identified BNP as a strong predictor of morbidity and mortality in the general population even when BNP levels were below the threshold normally used to diagnose patients with heart failure [3].…”
Section: Introductionmentioning
confidence: 99%
“…Use of b‐type natriuretic peptide (BNP) and the physiologically inert cleaved fragment, N‐terminal‐pro‐b‐type natriuretic peptide (NT‐proBNP), are guideline recommended by for the evaluation of dyspnea 2, 3. BNP and/or NT‐proBNP levels correlate with HF diagnosis, severity, and mortality 4, 5. However, obesity may be associated with lower circulating levels of BNP and/or NT‐proBNP 6, 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%